Hemodynamic Evaluation during Balloon Test Occlusion of the Sigmoid Sinus: Clinical and Technical Considerations - Ernemann, Ulrike; Löwenheim, Hubert; Freudenstein, Dirk; Koerbel, Andrei; Heininger, Alexandra; Tatagiba, Marcos (American Journal of Neuroradiology, 2005)
Summary: Test occlusion of a patent dural sinus requires careful hemodynamic evaluation. We performed balloon test occlusion of the sigmoid sinus in a patient with an advanced-stage temporal bone malignancy that affected the dominant sigmoid sinus. Before and during the test occlusion, intrasinus pressure was monitored upstream from the balloon via the inner lumen of a double-lumen angioplasty balloon microcatheter. On the basis of the hemodynamic findings, permanent balloon occlusion was carried out without complications.